Localised amyloidosis of the bladder: A rare mimic of urinary tract malignancy (case report and literature review). (2020) - Mayor, N.; Coppola, A.S.J.; Knights, Harry; Nazar, T.; Hunter, H.; Mostafid, H.
Highlights: Localised amyloidosis of the urinary tract is rare but invariably mimics urinary tract malignancy. Urologists should consider amyloidosis where malignancy is not evident. The disease is course is typically benign. Most patients can be treated conservatively, without radical surgery. This is the most up to date literature review describing the disease. Abstract: Introduction: Localised amyloidosis of the urinary tract is rare and often presents with haematuria. Presentation of case: A 59 year old male presented with recurrent episodes of frank haematuria exacerbated by anticoagulation after a minor stroke. He had a background of hypertension, hypercholesterolaemia, and Parkinson's disease. Initial investigations did not reveal a cause, but eventual cystoscopic biopsy showed bladder mucosa expanded by deposits of amorphous, pale, eosinophilic, proteinaceous material and immunohistochemical staining revealed the presence of amyloid deposition. Workup for systemic amyloidosis was negative. A diagnosis of primary localised amyloidosis of the bladder was made. Trans-urethral resection was performed and annual cystoscopic surveillance was commenced. He was followed up for 11 years without recurrence. Discussion: A comprehensive literature review revealed 349 published cases of localised amyloidosis of the urinary tract, with a median age of 57 (interquartile range 49–69), and a male preponderance (1.5 to 1). Painless visible haematuria (65%) was the most frequent presenting complaint and the bladder was the most common site of involvement (71%). Transurethral resection was the most common form of management (42%) but a proportion of patients underwent more radical surgery (nephroureterectomy/nephrectomy 9%, cystectomy 1%). Median follow up was 33 months (interquartile range 12–108) and 35% of patients had recurrent disease. This patient represents a typical case of localised amyloidosis of the urinary tract. Conclusion: This is the most up to date review of the literature describing localised amyloidosis of the urinary tract. The disease is rare, but salient to the urologist as it invariably mimics urinary tract malignancy.